OCORRÊNCIA DE Beauveria bassiana (Bals.) Vuill. EM ADULTOS DE Gonipterus scutellatus (Gyllenhal) (COLEOPTERA, CURCULIONIDAE) - Berti Filho, Evoneo; Alvez, Sérgio Batista; Cerignoni, João Angelo; Stape, José Luiz (REVISTA DE AGRICULTURA, 2015)
OCORRÊNCIA DE Beauveria bassiana (Bals.) Vuill. EM ADULTOS DE Gonipterus scutellatus (Gyllenhal) (COLEOPTERA, CURCULIONIDAE)